Tingkat Kepuasan Petani Terhadap Aspek Organisasi Gapoktan di Kecamatan Gandusari, Kecamatan Talun, Dan Kecamatan Kademangan - Edya moelia Moeis; Supardi Supardi (Jurnal Sains Peternakan, 2020)
This study aims to determine the satisfaction of farmers with the organizational aspects of Gapoktan (Farmers Groups Association) in Regency of Blitar. This study uses the RAL method (Completely Randomized Design). The number of respondents was 27 people, which were taken by proportional random sampling from 10 farmer groups registered in the Regency of Blitar. Respondents were given 7 point questions related to organizational aspects of Gapoktan. Each question has a cumulative assessment score that was represented by scoring level from 1 to 5 (very dissatisfied, dissatisfied, somewhat satisfied, satisfied, and very satisfied). The obtained result shows that farmers quite satisfied the organizational aspects of each respective farmer groups. Many factors affect the final results of the questionnaire given to respondents. The main factor is the understanding of respondents about the given problem and this understanding factor is strongly influenced by their level of education and age.